Innovations in Narrative and Metaphor Methodologies and Practices - Farquhar, Sandy; Fitzpatrick, Esther; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book pursues an interdisciplinary approach to open a discourse on innovative methodologies and practices associated with narrative and metaphor. Scholars from diverse fields in the humanities and social sciences report on how they use narrative and/or metaphor in their scholarship/research to arrive at new ways of seeing, thinking about and acting in the world. The book provides a range of methodological chapters for academics and practitioners alike. Each chapter discusses various aspects of the author's transformative methodologies and practices and how they contribute to the lives of others in their field. In this regard, the authors address traditional disciplines such as history and geography, as well as professional practices such as counselling, teaching and community work.
Innovations in narrative and metaphor -- 1 Narrative and metaphor: The beginning matter -- 2 narrative and Metaphor: The story of a network -- Writing as a craft -- 2 When I was Seventeen -- 4 Snowflakes, splinters, and cobblestones: Metaphors for writing -- 5 The case for faction as a potent method for integrating fact and fiction in research -- 6 Writing innovative narratives to capture the complexity of lived experiences: Poetry, scriptwriting and prose -- Ethics and rethinking narrative research -- 7 "Who said this?" Negotiating the ethics and politics of co-authorship in collaborative community text-making -- 8 Writing narratives of hope: An act of aroha -- 9 Reconfiguring narrative methodologies: Thresholds of realities in post-qualitative methodologies -- Metaphor and fictional devices -- 10 Snow White, a mirror and whiteness: Entangling thoughts in metaphors -- 11 Flow my tears, the teacher said: Science fiction as method -- 12 Placing narrative and metaphor in the flow of contemporary music:PJ Harvey's The Community of Hope -- Personal storytelling -- 13 Grief, loss and critical autoethnography: The father's tale -- 14 Narrative and educational change: The power of intentional interruption -- Performance and practice -- 15 An empty chair performs: Performative inquiry -- 16 A gap in the place where a teacher should be -- 17 Materializing memories as visual narrative: Voices from autoimmune and dementia settings.
Keywords: Educational sociology; Sociology -- Methodology; Education -- Philosophy; Sociology of Education; Sociological Methods; Educational Philosophy